SYSTEMS AND STRUCTURES OF THE JINAYAT QANUN AND ITS OPPOSING TEXTS - Anggraini T Saragih (UIN Sumatera Utara, 2016)
The Jinayat Qanun (JQ) as one of the qanuns issued and enforced by the Governments in the Aceh Province has resulted in opposing views by the stake holders at the provincial and national levels. The JQ and its opposing texts need studying by which objective descriptions can be obtained for the purpose of developmenal programs at the Aceh Province as a part of the Republic of Indonesia. This study is based on linguistic theories, which objectively describes the system, structure and linguistic realizations of the JQ and its opposing texts. This is a qualitatively descriptive study with texts, and descriptions of social contexts of the texts as the data. The data were obtained by collecting the JQ and its opposing texts and interviews. The data were then analyzed by using theories of text analysis commonly used in systemic functional linguistic (SFL) theories. The findings show that each of the two kinds of text has its own different system, stucture and linguistic realizations as each of which is related to different functions and social contexts. In other words, there have been various understandings of the two texts. By the various understandings of the two texts, views of the stake holders form proportionally; a condition which is highly needed in Indonesia as a democratic country. Key Words: qanun jinayat, Aceh, opposing views